"The whole elephant": "What works best" consultation practices of learning support teams in primary schools. Issue 2 (3rd July 2022) - Bryceson, Natasha; Sheridan, Lynn
ABSTRACT: This study explored the consultation practices of Learning Support Teams (LSTs) in three NSW primary schools engaged in learning and wellbeing support for diverse students. An organisational ethnographic case study approach was used to explore behaviour, language and interactions within the school sites. Participants included learning support teachers, senior executive staff, school counsellors and psychologists. To elicit specific practices from participants, an Interview to the Double technique was employed to collect qualitative data. Findings showed that teams used specific data-driven decision-making and problem-solving practices to address challenges in supporting student learning and wellbeing. LSTs identified shared purpose, effective membership structures, communication and relationships as critical in consultation. This study has implications for understanding "what works" for LST consultation and recognised the need for explicit measuring and monitoring of team impact.